Carotenoderma due to lycopenemia: A case report and evaluation of lycopene deposition in the skin. Issue 12 (8th August 2022) - Tanaka, Arisa; Miyauchi, Toshinari; Kitamura, Shinya; Iwata, Hiroaki; Hata, Hiroo; Ujiie, Hideyuki
Abstract: Carotenoderma is a yellow‐orange coloration of the skin caused by high levels of serum carotenoids, mostly due to the excessive intake of carotenoid‐rich foods. The yellowish coloration is typically observed on the palms, soles, and nasolabial folds. Although the physical appearance is prominent, the condition itself is benign and harmless. Diagnosing carotenoderma is not difficult because of its unique manifestations, but its pathophysiology remains unclear. We report a relatively rare case of carotenoderma due to lycopenemia caused by the excessive intake of lycopene‐rich vegetables and fruits. Lycopene is a carotenoid component that is distinguished by the high absorption of light around 488 nm. Given these characteristics, we examined a hematoxylin–eosin‐stained specimen from the patient and tape‐stripped samples by fluorescent microscopy with 488 nm wavelength emission and compared them with normal skin samples. Notably, the patient's samples showed a weaker autofluorescence in the stratum corneum and sweat glands. Furthermore, we measured carotenoid concentrations in the patient's skin noninvasively with Vegecheck® and found a higher score than the average of 24 healthy volunteers. These results support the long‐held hypothesis that carotenoids are secreted in sweat and are deposited in the stratum corneum. To the best of our knowledge, no previous reports have measured skin carotenoid levels nor detailed the pathological findings of carotenoderma patients. This case further highlights that the excessive intake of lycopene causes carotenoderma and demonstrates that carotenoid deposition is particularly pronounced in the stratum corneum of the skin.